Intravenous Thrombolysis by Telestroke in the 3- to 4.5-h Time Window - Simon, Erik; Forghani, Matin; Abramyuk, Andrij; Winzer, Simon; Wojciechowski, Claudia; Pallesen, Lars-Peder; Siepmann, Timo; Reichmann, Heinz; Puetz, Volker; Barlinn, Kristian; Barlinn, Jessica (Frontiers in Neurology, 2021)
Background: While intravenous thrombolysis (IVT) in ischemic stroke can be safely applied in telestroke networks within 3 h from symptom onset, there is a lack of evidence for safety in the expanded 3- to 4. 5-h time window. We assessed the safety and short-term efficacy of IVT in acute ischemic stroke (AIS) in the expanded time window delivered through a hub-and-spoke telestroke network. Methods: Observational study of patients with AIS who received IVT at the Stroke Eastern Saxony Telemedical Network between 01/2014 and 12/2015. We compared safety data including symptomatic intracerebral hemorrhage (sICH; according to European Cooperative Acute Stroke Study II definition) and any intracerebral hemorrhage (ICH) between patients admitted to telestroke spoke sites and patients directly admitted to a tertiary stroke center representing the hub of the network. We also assessed short-term efficacy data including favorable functional outcome (i.e., modified Rankin Scale ≤ 2) and National Institutes of Health Stroke Scale (NIHSS) at discharge, hospital discharge disposition, and in-hospital mortality. Results: In total, 152 patients with AIS were treated with IVT in the expanded time window [spoke sites, n = 104 (26.9%); hub site, n = 48 (25.9%)]. Patients treated at spoke sites had less frequently a large vessel occlusion [8/104 (7.7) vs. 20/48 (41.7%); p < 0.0001], a determined stroke etiology (p < 0.0001) and had slightly shorter onset-to-treatment times [210 (45) vs. 228 (58) min; p = 0.02] than patients who presented to the hub site. Both cohorts did not display any further differences in demographics, vascular risk factors, median baseline NIHSS scores, or median baseline Alberta stroke program early CT score (p > 0.05). There was no difference in the frequency of sICH (4.9 vs. 6.3%; p = 0.71) or any ICH (8.7 vs. 16.7%; p = 0.15). Neither there was a difference regarding favorable functional outcome (44.1 vs. 39.6%; p = 0.6) nor median NIHSS [3 (5.5) vs. 2.5 (5.75); p = 0.92] at discharge, hospital discharge disposition (p = 0.28), or in-hospital mortality (9.6 vs. 8.3%; p = 1.0). Multivariable modeling did not reveal an association between telestroke and sICH or favorable functional outcome (p > 0.05). Conclusions: Delivery of IVT in the expanded 3- to 4.5-h time window through a telestroke network appears to be safe with equivalent short-term functional outcomes for spoke-and-hub center admissions.